The efficacy of direct and indirect written corrective feedback in ESL learners’ writing / Sharina Azni Ahmad - Sharina Azni , Ahmad (2019)
The efficacy of WCF in ESL writing has become a debate due to the notion made by Truscott (1996) that WCF is ineffective in grammatical accuracy, and it also can give harmful effects to the learners. Subsequently, many researchers have been raising the issue of whether or not teachers should provide WCF in English classes in their studies (Pham, 2015; Shirazi & Shekarabi, 2014; Sheen, 2010; Bitchener & Knoch, 2009; Sachs & Polio, 2007; Ferris, 2006). However, findings from various studies were inconclusive due to the different ways of measuring the effectiveness. Hence, the purpose of this study is to find out the effectiveness of WCF in improving the accuracy of past tenses in ESL learners’ written work. In this study, the controversial issue of written corrective feedback (WCF) was examined through an eight-week longitudinal study approach. A pretest-posttest design was employed. 30 participants were divided into two groups, and they went through two treatment sessions and two posttests. The participants received WCF on three essays under two treatment conditions: Group (1) received direct WCF; and group (2) received indirect WCF on specific grammar errors. Descriptive writing, which involved picture compositions was the instrument employed for this study. ANOVA was used as the statistical means of analysis. The quantitative result showed that students who received direct WCF outperformed students who received indirect WCF in terms of writing accuracy. Face-to-face interview sessions were conducted with 12 students and the qualitative result revealed three main factors: 1) facilitative impact of WCF, 2) cognitive effort involved in understanding the errors, and 3) facilitative effect of scaffolding. The findings of this study will give insights to ESL teachers on which WCF to be used in students’ writing. However, the results of this study cannot be generalized in all schools in Malaysia because the data was collected in a school in Selangor only.